Hepatoprotection and Immunomodulation of Natural Killer and CD8 T Cells by Meniran-Turmeric Extract Combination in Mice Injected with 7,12-Dimethylbenz[a] Anthracene - Puspitarini, Sapti; Widodo, Nashi; Widyarti, Sri; Azzamuddin, Haidar; Ulinnuha, Maria; Puspitoputri, Alya H.; Khansa, Shafanony; Rifa’i, Muhaimin (HAYATI Journal of Biosciences, 2026)
Combination herbal or polyherbal offers advantages by synergizing multiple plants to address health issues more effectively. Meniran and turmeric are traditionally used medicinal plants with notable pharmacological activities due to their bioactive compounds. This study investigated the curative effect of a meniran-turmeric extract combination on immunocompetent cells, particularly NK and CD8 cells, and on liver histopathology in mice administered 7,12-dimethylbenz[a]anthracene (DMBA). Female BALB/c mice (Mus musculus) were injected subcutaneously with DMBA at 45 mg/kg body weight (BW) in the mammary gland area and maintained for eight weeks. They were then treated with a 1:1 meniran-turmeric extract combination for two weeks at doses of 100, 300, 900, and 1,800 mg/kg BW, followed by liver and immune cell analyses. The results showed a lower CD8+ T-cell population in extract-treated groups (17.53±1.13%-19.79±1.51%) compared with the DMBA group (20.92±4.74%). Conversely, NK+ cell populations increased after extract treatment (0.33±0.01%-0.56±0.13%) compared with DMBA alone (0.27±0.02%). Liver histopathology indicated that extract combination administration did not cause more severe damage than that observed in the DMBA group. An extract combination of meniran and turmeric could modulate the immune system, particularly NK and CD8 cells, in mice injected with DMBA. In addition, the study indicated that the combination of meniran and turmeric extract might play a role as an antihepatotoxic agent. This research could serve as a consideration for future studies developing a combination formulation of meniran and turmeric.